2014
DOI: 10.4103/0971-6580.139800
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of various biochemical parameters in acute organophosphorus poisoning

Abstract: Background:Organophosphorus (OP) compounds are a heterogeneous group of insecticides widely used in agricultural industry. These OP compounds are likely to have more adverse effects in developing countries like India due to its easy availability and less awareness which results in high morbidity and mortality.Aims and objectives:1. To estimate plasma cholinesterase, amylase, lipase and, creatine phosphokinase (CPK) in acute OP poisoning. 2. To correlate these biochemical parameters with plasma cholinesterase l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 11 publications
12
25
1
Order By: Relevance
“…Thus this increase in serum amylase level was coinciding with severity, the same result was reported by Alawadi (2000). These results go with Sumathi et al (2014) who reported significant association with severity of OP poisoning with respect to amylase and lipase.Serum amylase and lipase can be used as a marker for recognition of severity in op poisoning (Adhil and Sudharsan, 2015). Serum amylase levels may be considered as a marker of Organophosphorous intoxication, since it enables the early recognition of severity and to identify those at risk of developing the complications of Organophosphorous poisoning (Salame and Wani, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Thus this increase in serum amylase level was coinciding with severity, the same result was reported by Alawadi (2000). These results go with Sumathi et al (2014) who reported significant association with severity of OP poisoning with respect to amylase and lipase.Serum amylase and lipase can be used as a marker for recognition of severity in op poisoning (Adhil and Sudharsan, 2015). Serum amylase levels may be considered as a marker of Organophosphorous intoxication, since it enables the early recognition of severity and to identify those at risk of developing the complications of Organophosphorous poisoning (Salame and Wani, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Banerjee et al (2012) postulated in their study that male to female ratio was 1:1.38. On contrary to many other studies males were more affected than females (Muley et al, 2014;Sumathi et al, 2014;Ghaniger et al, 2016).Causes of female predominance in the current study may be attributed to emotional liability of female to life stress and strains in our society than male also due to easy availability of OP compounds in the home as a household product (Z'gambo et al, 2016).…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations